(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
This article analyzes the history of the formation of the Shanghai Cooperation Organization, the stages of its development, and the role and role of this organization in ensuring regional security and economic cooperation. They talked about the organization’s Samarkand summit and the issues discussed there.